N6-methyladenosine regulates metabolic remodeling in kidney aging through transcriptional regulator GLIS1 - Li Xu; Shuo Chen; Qiuling Fan; Yonghong Zhu; Hang Mei; Jiao Wang; Hongyuan Yu; Ying Chen; Fan Liu (BMC Biology)
Abstract Background Age-related kidney impairment, characterized by tubular epithelial cell senescence and renal fibrosis, poses a significant global public health threat. Although N6-methyladenosine (m6A) methylation is implicated in various pathological processes, its regulatory mechanism in kidney aging remains unclear. Methods An m6A-mRNA epitranscriptomic microarray was performed to identify genes with abnormal m6A modifications in aged human kidney tissues. Histological, immunohistochemical, and immunofluorescent staining, western blot, and RT-qPCR were employed to examine the biological functions of targeted genes and m6A methyltransferases both in vivo and in vitro. RNA immunoprecipitation, chromatin immunoprecipitation, ribosomal immunoprecipitation, and luciferase reporter assays were used to investigate the specific interactions between m6A methyltransferases, targeted genes, and their downstream signals. Results Significantly lower m6A modification levels were observed in aged human kidney tissues. GLIS1, identified as a “metabolic remodeling factor,” showed significantly reduced protein levels with abnormal m6A modifications. The downregulation of GLIS1 induced cell senescence and renal fibrosis by shifting metabolic remodeling from fatty acid oxidation (FAO) to glycolysis. Additionally, the methylated GLIS1 mRNA was regulated by the abnormal expression of METTL3 and YTHDF1. Silencing METTL3/YTHDF1 weakened the translation of GLIS1 and disrupted the balance between FAO and glycolysis. Conclusions Our findings suggest that the m6A modification of GLIS1, activated by METTL3 and reduced in a YTHDF1-dependent manner, leads to kidney aging by regulating the metabolic shift from FAO to glycolysis. This mechanism provides a promising therapeutic target for kidney aging.